Randomized Trial of Fetal Surgery for Severe Left Diaphragmatic Hernia. Issue 12 (December 2021) - Deprest, Jan A.; Nicolaides, Kypros H.; Benachi, Alexandra; Gratacos, Eduard; Ryan, Greg; Persico, Nicola; Sago, Haruhiko; Johnson, Anthony; Wielgoś, Mirosław; Berg, Christoph; Van Calster, Ben; Russo, Francesca M.
Abstract : (Abstracted from N Engl J Med 2021;385:107–118) Congenital diaphragmatic hernia (CDH) occurs in approximately 1 in 4000 births, and 85% of these cases have the defect on the left side. The condition is associated with neonatal death due to respiratory failure and pulmonary hypertension.